Development of a field-portable digital potentiostat (2012)
The use of potentiostats for corrosion rate studies and activation polarization is very crucial because the weight loss method is limited in corrosion studies. However, commercial potentiostats are expensive for most end users. For these reasons, it was desirable to design and build an inexpensive field-portable potentiostat to interface with electrochemical cell. This paper present the proceeudre and design principles of a portable, digital and inexpensive potentiostat, its construction and testing PROTEUS software was used in the design of the different components of the potentiostate and simulation of the tested in a corrosion cell in which a mild steel working electrode (WE) was immersed in 5% NaCl solution. Ag/ AgCl exchange current density (io of mild steel, |Fe/Fe2) of 1.5 X10-6 A/ cm2, standard potential of ,mild steel (Eo mildsteel) of -0.42V and corrosion penetration rate (CPR) at io of 9.18x10-7 cm/hr and Taffel β value of 0.13V was obtained for mild steel in 5% NaCl solution. The values of OCP, ioEo, CPR and β were consistent with values obtained form literature.